The Role of Corporate Social Responsibility on the Performance of Indonesian Banking Corporation - Hamzah, Ruth Samantha; Gozali, Efva Octavina Donata; Annisa, Mutiara Lusiana; Pratiwi, Chomsah Novianti (Goodwood Publishing, 2022)
Purpose: The study employs Corporate Social Responsibility (CSR) as a moderating variable. We aim to discover the role of CSR on the influence of audit firm rotation (AFR), audit committee gender (ACG), and audit quality (AQ) on banking performance. Methodology/approach: The regression analyses were performed multiple and moderated to exploit the linear model and moderating model, respectively. Results/findings: The results show that ACG has a significant effect on banking performance, meanwhile AFR and AQ have no significant influence on banking performance. Furthermore, the results of the moderated regression analysis revealed that CSR cannot moderate the influence of AFR, ACG, and AQ on banking performance. Limitations: We limited the variables only in terms of AFR, ACG, and AQ for the direct influence on firm performance. Therefore, we did not include determinant variables of firm performance in the model (e.g., firm size, firm age, firm growth, financial ratio). We suggest for further research include these determinant variables as a control variable. Contribution: The study delivers understanding and information on behalf of the influence of AFR, ACG, and AQ on firm performance, particularly for the banking sector in emerging countries. In addition, this research has implications for regulators to improve banking performance. Novelty: We use CSR as a moderating role. To the best of our knowledge, there is no prior study that employs CSR as a moderating role among AFR, ACG, and AQ association to banking performance. Meanwhile, previous studies prove the strong relationship between CSR to banking performance.